Merging Scientific Silos: Integrating Specialized Approaches for Thinking about and Using Spatial Data That Can Provide New Directions for Persistent Fisheries Problems. Issue 10 (11th August 2021) - Mather, Martha E.; Smith, Joseph M.; Boles, Kayla M.; Taylor, Ryland B.; Kennedy, Cristina G.; Hitchman, Sean M.; Rogosch, Jane S.; Frank, Holly J.
Abstract : By merging our specialization silos, fisheries professionals can expand the options that are available to them to address difficult fisheries and aquatic conservation problems, which require an understanding of spatial patterns in geographically large systems. Our purpose is to start a profession‐wide conversation about additional ways to think about and use spatial data. We use case studies to illustrate how identifying and merging multiple specialized approaches (e.g., fish tracking, fish surveys, geomorphology, social science, jurisdictional viewpoints) can create an ensemble that has advantages over the use of any single approach alone. Thus, our perspective is not about solving a specific technical problem with a new tool, but about the benefits of identifying gaps in data from one specialized approach, and filling those gaps with data from other specialized approaches. If multiple approaches are coordinated through a larger, problem‐specific planning strategy, the result can be better outcomes for difficult problems through creative integration. We encourage others to add constructive ideas to the views initiated here.